Effect of dietary vitamin E and organic selenium supplementation on reproductive performance of Japanese quail breeders - P. Chitra (Indian Journal of Veterinary and Animal Sciences Research, 2025)
This study was conducted to evaluate the effect of different dietary level of vitamin E and organic selenium on the reproductive performance of Japanese quail breeders. A total of 252 Japanese quail birds aged 20 week with an average of 80 per cent egg production were used in this study. Trial birds were randomly divided into seven groups having male: female mating ratio of 1:3. Experimental birds were randomly divided into seven groups viz. T1- Control: Basal diet (standard Japanese quail ration), T2 - Basal diet with vitamin E 150mg/kg, T3 - Basal diet with vitamin E 300 mg/kg, T4 - Basal diet with organic selenium 0.3mg/kg, T5 - Basal diet with organic selenium 0.6mg/kg, T6 - Basal diet with combination of vitamin E 150mg/kg and organic selenium 0.3mg/kg, T7 - Basal diet with combination of vitamin E 300mg/kg and organic selenium 0.6mg/kg. The highest fertility (91 percent) and hatchability (Total eggs 80 percent; fertile eggs 89 percent) percentage were observed in experimental group which received vitamin E 150 mg per kg and selenium 0.3 mg per kg while the least fertility (78 percent) and hatchability (Total eggs 62 percent; fertile eggs 80 percent) percentage were recorded in the control group. From this study it can be concluded that dietary supplementation of vitamin E and organic selenium had highly significant (P